Justification In Arabic Critical And Rhetorical Discourse Its Forms And Foundations/ التعليل في الخطاب النقدي والبلاغي العربي أشكاله وأصوله - Riyadh Mohammmad Okaidy; Mohannad Shabeeb Hamad Al-Fahdawy (Ijaz Arabi Journal of Arabic Learning, 2026)
This study examines justification in Arabic critical and rhetorical discourse as a fundamental tool employed by critics and rhetoricians to justify evaluative judgments, interpret literary texts, and establish critical and rhetorical principles. The development of justification is closely linked to the evolution of Arabic knowledge, which shifted from sensory-based cognition to rational inquiry grounded in reflection and inference. Early critical judgments, particularly before and at the onset of formal authorship, were often presented without explicit justification. However, with the maturation of Arabic intellectual traditions, scholars increasingly sought to justify such judgments and became less inclined to accept them without supporting arguments. Consequently, justification emerged as an essential means of reinforcing and validating judgments, enhancing their persuasive force and ensuring their acceptance, as justified claims are more compelling than unsupported assertions. Moreover, justification contributed to the development of critical and creative thinking by encouraging inquiry into the grounds upon which judgments are based. It also assumed diverse forms and was influenced by related disciplines, including theology (kalām), legal theory (uṣūl al-fiqh), and grammar (naḥw). In addition, theological orientations played a significant role in shaping justificatory practices, particularly in the interpretation of religious texts and discussions of the inimitability of the Qurʾān.